CRISIS MANAGEMENT TROUGH PRISM OF NATO (Annual of the Faculty of Philosophy in Skopje, 2008)
Crisis management and conflict prevention, have been major themes in the continuing transformation of the Alliance after the Cold War. In the new circumstances there are new possibility for the successful early management of crises. NATO's preparedness to carry out crisis management operations, usualy includes the participation of NATO's Partners and that makes full use of partnership, cooperation and dialogue and NATOs conection to other organizations to help in preventing crises or defusing them at early stage. According to Washington Treaty, NATO has been managed the crisis and prevented conflicts since its begining. With the drasticall change of the security environment, the types of crises which allies have agreed should manage and the types of conflicts to prevent, also changed drastically The term NATO crisis management has also evolved. A key need of a NATO's crisis management system, is the power to manage with crises throughout the entire crisis variety. It includes the period of stability and peace before crisis as well as all levels of crisis. NATO has built a spectrum of general elements to help crisis management and conflict prevention: personal and objects; arrangements and procedures; and measures. For timely response to a crises, NATO concluded that it is very important to have prepeared a variety of different activities in place so that they do not have to be formed on an ad-hoc basis for each new potencial or actuel crisis.
Keywords: CRISIS; MANAGEMENT; CONFLICT; PREVENTION